Keterlibatan Belajar Siswa dan Berpikir Kreatif pada Siswa Introver dan Ekstrover - Fauziah Noor Khalifah; Ridwan Budi Pramono (Buletin Riset Psikologi dan Kesehatan Mental, 2023)
Student learning engagement and creative thinking are important in education. Based on the preliminary study result, it is known that students have a moderate to low level of student learning engagement and creative thinking. This study aims to determine the differences in student learning engagement and creative thinking in introverted and extroverted students. The study was conducted on vocational high school students in Kudus with 96 total research participants consisting of 48 introverted students and 48 extroverted students. The measuring instrument used to obtain data is using the DISC test tool, student learning engagement scale, and creative thinking scale. The results of data analysis show that there are differences in student learning engagement in introverted and extroverted students (p=0.012), where introverted students have higher levels of students learning engagement (M=90.48) than extroverted students (M=84.21). However, in the creative thinking variable, there are no differences between introverted and extroverted students (p=0.870).